Timing and extent of Quaternary glaciations in the Tianger Range, eastern Tian Shan, China, investigated using Be-10 surface exposure dating - Li, Yingkui; Liu, Gengnian; Chen, Yixin; Li, Yanan; Harbor, Jon; Stroeven, Arjen P.; Caffee, Marc; Zhang, Mei; Li, Chuanchuan; Cui, Zhijiu (Quaternary Science Reviews, 2014)
Reconstructing glacial chronologies with consistent methods is critical for efforts to examine the timing and pattern of past climate change. Cosmogenic Be-10 surface exposure dating has been widely used to constrain the timing of glacial events on the Tibetan Plateau and in Central Asia. However, few such studies have been conducted in the Chinese Tian Shan and available Be-10 ages from this region have only provided evidence for glacial events during the global Last Glacial Maximum (gLGM) and Lateglacial. Here, we present 45 Be-10 surface exposure ages from glacial landforms in the Ala and Daxi valleys, two formerly glaciated valleys draining the Tianger Range, eastern Tian Shan. Combined with previously published Be-10 surface exposure ages from the Daxi Valley in the source area of the Urumqi River, the new ages record five major glacial events during Marine Oxygen Isotope Stages (MIS) 6 or older, 4, 3, 2, and 1 (during the Little Ice Age, LIA). Landforms from glacial events since MIS 2 are found on the northern slope of the Tianger Range (Daxi Valley), whereas evidence for the older glacial events is only preserved on its southern slope (Ala Valley). This disparity may be caused by different preservation- and micro-climatic conditions on the northern and southern slopes of this mountain range, due to differences in gradient and aspect. The LIA glacial advances are apparently the only Holocene glacial event recorded in this area. Earlier Holocene glacial events were probably so restricted in extent that they were destroyed by subsequent LIA advances. (C) 2014 Elsevier Ltd. All rights reserved. Geography, Physical Geosciences, Multidisciplinary SCI(E) EI 2 ARTICLE yli32@utk.edu 7-23 98